Managerial economics - Mixon, J. Wilson; Uri, Noel D. (New York : Macmillan ; London : Collier Macmillan, 1985)
"Managerial Economics, Fourth Edition, has been thoroughly updated and revised to reflect the complex business environment within which today's managers make decisions. Professors Petersen and Lewis provide students with a complete introduction to the basic principles of microeconomics while demonstrating how application of economic theory can improve management decision making. This approach involves first introducing the basic concepts of managerial economics and then using the principles to analyze decisions faced by managers. Numerous case studies and solved problems are included throughout the book to highlight the application of important principles.
Includes bibliographical references and index.
aia 04/05/2018
Loans
Keywords: Managerial economics; Microeconomics